Difference of mandibular trabecular bone fractal dimension values on panoramic radiographs of vegetarians and nonvegetarians in Medan City - Kartika, Dewi; Manja, Cek Dara; Wulandari, Pitu; Salamatusshodri; Sidabutar, Herlina (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Vegetarians are known to be more susceptible to experiencing bone mineral density decreases compared to nonvegetarians. The trabecular bone is sensitive to any changes that disrupt the balance of bone metabolism. On panoramic radiographs, bone density can be evaluated by analyzing the fractal dimensions (FD) of the mandibular trabecular bone. Purpose: This analytical cross-sectional study aimed to assess the mandibular trabecular bone FD values on panoramic radiographs of vegetarians and nonvegetarians in Medan City. Methods: This study used a purposive-sampling technique and obtained 30 digital panoramic radiographs of vegetarians and nonvegetarians in Medan City, aged 20 to 40 years, between January and February 2023, at the radiology installation of Dental and Oral Hospital Universitas Sumatera Utara and Laboratory Clinic Pramita Medan. Fractal analysis was performed using ImageJ 1.54c software with the box-counting method. The data distribution was assessed using the Shapiro–Wilk test. The data were analyzed using an independent samples T-test. Results: The results showed that the FD values of the mandibular trabecular bone were significantly different between the two groups (p = 0.000). Conclusion: The mean FD values on the panoramic radiographs were lower in the vegetarian mandibular trabecular bone than in the nonvegetarian mandibular trabecular bone. Considerations need to be made by dentists when performing treatments related to mandibular trabecular bone surgery in vegetarians.